Silence Is Golden. Six Reasons Inhibiting the Spread of Third-Party Gossip - Giardini, Francesca; Wittek, Rafael P. M. (Frontiers in Psychology, 2019)
Most of the current literature on gossip describes gossipmongers as incessantly sharing evaluative and valuable information about an absent third party in teams, groups, communities, and organizations. However, potential gossipers can similarly decide not to share what they know, depending on the content, the context, or their relationship with the other actors in the gossip triad. We argue that understanding the reasons why people do not gossip may provide useful insights into individual motives, group dynamics, and collective behaviors. This theoretical contribution first critically surveys the existing gossip literature with the aim of highlighting the conditions under which people might refrain from sharing third party information. We then propose to apply Goal Framing theory as a way to bridge a theory of the micro-foundations of human behavior with an analytical model of the gossip triad that disentangles the various ways through which senders, receivers, and objects of gossip may be interrelated. From a goal framing perspective, most research on gossip illustrates the mechanisms in which the hedonic gratification derived from gossiping is reinforced by gain or normative goals. However, a normative or a gain goal frame can prevent the gossip monger from spreading the information, and we argue that depending on different configurations of frames and relations between actors the perceived costs of sending gossip may be far higher than much of the previous literature suggests.